Economic Transition, Entrepreneurial Capacity, and Intergenerational Distribution - Rutherford, Thomas (IMF Working Papers; Working Paper ;, 2002)
A defining feature of transition economies is the expansion of the private sector. Motivated by the observation that new enterprises in transition economies seem to have a strong preference for recruiting young people, this paper studies intergenerational redistribution following from market reforms that stimulate private sector activity and firm creation. We implement a theoretical model and find that in some cases more than half of the current working age population may be made worse off by an increase in entrepreneurial capacity. This may help explain why market reforms have been voted down despite their long-run benefits.